2013
DOI: 10.1016/j.enpol.2013.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of green electricity tariff uptake in the UK

Abstract: A number of countries offer domestic consumers the option of buying their electricity supply through a 'green tariff', whereby the supplier typically guarantees that all or part of the supply has been generated using renewable energy sources. Various studies have sought to identify variables describing and/or predicting why domestic consumers choose to purchase a green tariff. This study builds on previous work by reviewing the UK market in particular. Using data from the Understanding Society Survey (USS), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 13 publications
(9 reference statements)
0
19
0
1
Order By: Relevance
“…Longhi (), for example, used these data and found that women have higher proenvironmental behaviour than men, and having a university degree also has a positive correlation with proenvironmental behaviour. MacPherson and Lange () used one of the indicators, exploring the determinants of green electricity tariff uptake in the UK . Thomas et al .…”
Section: Datamentioning
confidence: 99%
“…Longhi (), for example, used these data and found that women have higher proenvironmental behaviour than men, and having a university degree also has a positive correlation with proenvironmental behaviour. MacPherson and Lange () used one of the indicators, exploring the determinants of green electricity tariff uptake in the UK . Thomas et al .…”
Section: Datamentioning
confidence: 99%
“…While links between WTP for green energy and environmental awareness [36][37][38][39][40][41], between WTP and pro-environmental behavior [39,40,[42][43][44] and between WTP and knowledge [38,[44][45][46][47] have been found in previous studies, we judged these to be of a second-order effect and chose to focus on those attributes that could factor directly into marketing campaigns and could most easily be used to guide energy policy.…”
Section: Methodsmentioning
confidence: 99%
“…If people acknowledge that climate change exists and that they can contribute to its mitigation through a more environmentally conscious way of life, they often show an increased preference for green electricity [57]. MacPherson and Lange [58] revealed that people with high income, Green Party supporters, and people with very environmentally conscious behavior in their everyday life have more often switched to green electricity tariffs in the past. Kotchen and Moore [59] also noted that specific personal characteristics, such as environmental awareness, have an influence on the adoption of a green electricity tariff.…”
Section: Environmental Awareness and Personal Lifestylementioning
confidence: 99%
“…It seems obvious that people with a high awareness regarding environmental and sustainability issues are more likely to be interested in buying green electricity [53,56,57]. One way to gain information about consumer awareness is to ask whether participants are Green Party supporters [58]. In this study, the question was raised whether participants feel represented by the political platform of the Green Party.…”
Section: Hypothesis 4 -Environmental Awareness and Personal Lifestylementioning
confidence: 99%